IFPRI Nexus SAMs: Annual release note 2025 - International Food Policy Research Institute (International Food Policy Research Institute, 2025)
The Nexus Project is pleased to provide an update on Nexus Social Accounting Matrices (SAMs) developed and released by IFPRI in collaboration with national statistical agencies and research institutions in 2025. This Annual Release Note briefly overviews SAMs and the Nexus Project. It serves as a useful one-stop shop for obtaining links to all the latest versions of all Nexus SAMs.